Effect of E-Leadership Practices on the Performance of Teachers - Noreen Kousar; Dr. Wajiha Kanwal; Dr. Khalid Mehmood; Sobia Bibi; Afsheen Riaz (Journal of Management Practices, Humanities and Social Sciences, 2022)
This study aimed to examine the effects of e-leadership practices on teachers' performance and the general e- leadership practices in the schools of Taxila, Pakistan. The study's main objectives were to examine effects e-leadership practices have on performance teachers' performance, analyze the challenges faced by teachers, and illustrate prevailing e-leadership practices in the schools of Taxila. The population of the study contains 110 teachers from the high schools of Taxila. 10% of the male teachers and 15% of the female teachers were chosen using the persuasive sampling technique for the purpose of data collection. A questionnaire was used as a research instrument to collect the data for the measurement of variables. The data were tabulated, analyzed, and interpreted using SPSS software. The mean, percentage, standard deviation, regression test, descriptive statistics, and ANOVA test were used to look at the data in light of the study's goal. The study analyzed the findings according to the categories. According to the findings, e-leadership positively impacts the teachers' performance. Yet, the teachers face issues due to inadequate resources, improper training, technical faults, and improper guidance. Due to such issues, the satisfaction level of the teachers with e-leadership practices is impacted. The study explores the implementation of the e-leadership model in educational institutions and its effect on teachers' performance. The study is significant to define the challenges teachers face in the e-leadership model.